Preparation and adsorption behaviour of hydrophilic adsorbents using high internal phase emulsions - Işılgan, Bora (Graduate School, 2025)
Water pollution is one of the most major problems for a sustainable life. Especially dyes, which are one of the biggest sources of wastewater, also pollute the environment significantly. The large amounts of dyes produced in industries into water resources causes this problem to arise, for example, about 7 × 107 tons of synthetic dyes were produced. At this point, especially textile industries use about 10,000 tons of dyes per year, causing the dye solution to leach into water sources. Another negative impact of wastewater resulting from the dye solution is that discharging as wastewater into aquatic environments poses serious ecotoxicological threats on living organisms. Besides fish, other aquatic organisms such as microalgae are also adversely affected by dye wastes, the consumption of these can cause human health problems such as cramps, fever and hypertension. Methylene Blue is a cationic dye widely used in various textile fabrics and its chemical structure contains aromatic amines, potentially causing carcinogenic, toxic effects and non-biodegradable can cause a serious threat to human health. In the view of ecological effect, it decreases oxygen solubility, affects the photosynthetic activity of aquatic life, and decreases the diversity inhibits the synthesis of chlorophyll after dye exposure and reduces photosynthetic rate and consequently the photosynthetic activity of aquatic life. That is why, the removal of methylene blue is essential to the removal of methylene blue is essential to reduce impacts on the environment and living organisms. Adsorption is a suitable method for the removal of dye particles in waste materials. The fact that the structure of the adsorbent has a decisive role on the progress of adsorption makes the synthesis method of adsorbent important. One of the method production of adsorbent is high internal phase emulsion composed of external and internal phase forming 74 % or more of emulsion, which is a versatile technique based on adjusting pore volume, pore size and distribution. In this thesis, crosslinked highly porous volume polymers were prepared with a high internal phase emulsion method (HIPE). Polymerization of the external aqueous phase composed of monomers with 80% organic internal phase gave a flexible and elastic monolith polyHIPE structure and after extraction of internal phase then powdered. The presence of sulfonic groups in the monomer structure provided no longer need of modification steps and enabled loading of high functionality on pore structures. To evaluate the methylene blue adsorption on based polyhipe adsorbents, a variety of parameters were used to detect its effect on adsorption capacity. As as result of all adsorption experiments, the maximum adsorption capacity of the adsorbent was, found as 1483 mg/g for methylene blue, pseudo second order kinetic and langmuir isotherm were obtained more convenient compared to pseudo first order kinetic and freundlich isotherm.
Boya adsorpsiyonu için yüksek iç faz emülsiyonlari ile hidrofilik adsorbentlerin hazirlanmasi ve adsorpsiyon özellikleri
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: adsorbents; adsorbentler; adsorption; adsorpsiyon